Clinical Features and Outcomes of Repeated Endoscopic Therapy for Esophagogastric Variceal Hemorrhage in Cirrhotic Patients: Ten-Year Real-World Analysis - Jia-li Ma; Ling-ling He; Ping Li; Yu Jiang; Ju-long Hu; Yu-ling Zhou; Xiu-xia Liang; Hong-shan Wei (Gastroenterology Research and Practice)
Objective. This study is aimed at evaluating the survival of cirrhotic patients with different etiologies after endoscopic therapy for acute variceal bleeding and the effect of repeated endotherapy on patients’ prognosis. Methods. We retrospectively evaluated the clinical features and outcomes between cirrhotic patients with chronic HBV or HCV infections and other etiologies. The 3-year and 5-year survival rates and rehemorrhage rate in one year between the viral and nonviral cirrhosis patients were compared by Kaplan-Meier curves and log-rank test. Cox analysis was used to identify the impact factors that affect the long-term survival of patients with cirrhosis and variceal bleeding after endotherapy. Results. Out of 2665 patients with liver cirrhosis and variceal hemorrhage selected from our medical center between September 2008 and December 2017, a total of 1342 patients were included for analysis. The median follow-up duration was 32.9 months (range 0.16-111.4 months), the 3- and 5-year cumulative survival rates were 75.3% and 52.8%, respectively. The median survival time was significantly longer in viral cirrhosis patients (47.1 months [95% CI: 24.9-69.1]) compared with nonviral cirrhosis patients (37.0 months [95% CI: 25.0-56.0], p=0.001). The 3-year and 5-year survival rates of the viral group were higher than the nonviral group. The rehemorrhage rate at one year was higher in nonviral patients than in viral patients (p<0.001). Conclusion. Repeated endotherapy combined with effective antiviral therapy is helpful for long-term survival of cirrhotic population with variceal hemorrhage and HBV or HCV infection.